Phosphofructokinase 1 Platelet Isoform Promotes β-Catenin Transactivation for Tumor Development - Lee, Jong-Ho; Shao, Fei; Ling, Jinjie; Lu, Sean; Liu, Rui; Du, Linyong; Chung, Jin Woong; Koh, Sang Seok; Leem, Sun-Hee; Shao, Jichun; Xing, Dongming; An, Zhiqiang; et al. (Frontiers in Oncology, 2020)
Metabolism plays a critical role in direct regulation of a variety of cellular activities via metabolic enzymes and metabolites. Here, we demonstrate that phosphofructokinase 1 platelet isoform (PFKP), which catalyzes a rate-limiting reaction in glycolysis, promotes EGFR activation-induced nuclear translocation and activation of β-catenin, thereby enhancing the expression of its downstream genes CCND1 and MYC in human glioblastoma cells. Importantly, we showed that EGFR-phosphorylated PFKP Y64 has a critical role in AKT activation and AKT-mediated β-catenin S552 phosphorylation and subsequent β-catenin transactivation and promotion of tumor cell glycolysis, migration, invasion, proliferation, and brain tumor growth. These findings highlight a novel mechanism underlying a glycolytic enzyme-mediated β-catenin transactivation and underscore the integrated and reciprocal regulation of metabolism and gene expression, which are two fundamental biological processes in tumor development.